SEH AMONGRAGA’S MORAL TEACHINGS OF ISLAM IN SERAT CENTHINI - Sutrisna Wibawa (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2014)
This study discusses the Seh Amongraga’s moral teachings of Islam in Serat Centhini. Because of the breadth of Islamic moral teachings of the content delivered by various figures, then this study is limited in the moral teachings of Islam which was delivered by Seh Amongraga to his wife named Tambangraras. The results of this study are the moral teachings of Islam of Seh Amongraga’s moral philosophy is the realization of Java on the perfection of life sciences (ngelmu kasampurnan) as well as the science of the origin and direction of existing (sangkan paraning dumadi) which is the core of the moral philosophy of Java. Perfect life and behavior of guiding human thought in contemplating himself to find integrity in relationship with God. Origin and direction of human life that is guided and united in moving toward self-perfection of manunggaling kawula Gusti.